Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa FEBI UINSU Dalam Menggunakan Uang Elektronik Pada Aplikasi Dana - ‘Alimah, Nur; Marliyah, Marliyah; Fadhila Rahma, Tri Inda (Jurnal Manajemen Akuntansi (JUMSI), 2022)
The development of Information Technology and communication affects changes in the way of transactions, from the payment system using cash itunai Ike payment instrument inon itunai i(electronic ipayment isystem). this article provides acceleration in ibertransaction iterhadap imasyarakat iluas ipada umum. The use of an effective electronic ipayment system will have an impact on the reduced use of iunai I iignifikan money in itransaksi imahasiswa. This study aims to determine the influence of various expectations of work, business expectations and social influence on student interest in using the iDANA application. this research uses an analytical approach with a population of i5. 014 and uses icluster irandom isampling technique, which means that the use of random sampling is done by sending iform filling I random isesioner ike I the Ifebi iuinsu student image. isampled in this research i98 number iorang imahasiswa iFEBI iUINSU. The results of the research showed that isimultan using iuji if ivariable iEkspektasi performance, iekspektasi iUsaha idan I isosial ikerpaktur isignifkan iterhadap imahasiswa iFEBI iuinsu iekspektur iaplikasi iDANA. Iexpektasi performance imemiliki I influence ipositif iterhadap iMinat iminat iminat iminat iminat I0,320, iexpektasi performance imemiliki ipositif iterhadap iminat iminat I0, 320, iexpektasi iUsaha imemiliki inisai ipositif iterhadap Iminat iminat I0, 203. With this ir iSquare isebesar i0, 636 which means that the expectations of work, business expectations and social influence affect the interest of Ifebi iuinsu students isebesar i63, 6%.